ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL - Anila Madhyaratri, 09.05.52.0080; Wardjono, Wardjono (Students Journal of Accounting and Banking, 2013)
This research aims to analyze the effect of tangibility, return on assets, return on equity, and size of debt to assets on LQ-45 Companies Registered In Indonesia Stock Exchange. Samples were taken with purposive sampling by 75 observations. Data were analyzed using multiple linier regression, the data must by normally distributed, and the classical assumption free on multikolinierits, autokorelasion, and heterokadasitas. Goodsness fit with coefisien determition, and F test, and hypotesis testing by t test. This results of study to test the F-test statistics showed that between independent variables jointly effect the capital structure. From the results of hypotesis testing showed that tangibility variable has a not significant negative effect, return on assets variable has a significant negative effect, while the return on equity and size variables have a significant positive impact to capital structure.Keywords: Tangibility, Return on Assets, Return on Equity, Size, and Debt to Assets